Metabolic and Biochemical Stressors in Diabetic Cardiomyopathy - Kain, Vasundhara; Halade, Ganesh V. (Frontiers in Cardiovascular Medicine, 2017)
Diabetic cardiomyopathy (DCM) or diabetes-induced cardiac dysfunction is a direct consequence of uncontrolled metabolic syndrome and is widespread in the US population and worldwide. With several multifactorial and distinct features, the clinical relevance of DCM is now becoming established. DCM progresses to pathological cardiac remodeling with the higher risk of heart attack and subsequent heart failure in diabetic patients. In this review, we emphasize lipid substrate quality and the phenotypic, metabolic and biochemical stressors of DCM in the rodent and human pathophysiology. We discuss lipoxygenase signaling in the inflammatory pathway with multiple contributing and confounding factors leading to DCM. Additionally, emerging biochemical pathways are emphasized to make progress towards therapeutic advancement to treat DCM.